BANK SECTOR FINANCIAL SECURITY NATURE AND DECOMPOSITION - Fedorushchenko, Bohdan (Socio-economic relations in the digital society, 2020)
The aim of this study is to emphasize the importance of ensuring the bank sector financial security for the national economy. The importance of ensuring the financial security of the banking sector of the national economy is emphasized. The degree of coverage of this issue in the economic literature is clarified. The argumentation of the importance of observance of financial security of the banking sector of the national economy is given and the list of factors and preconditions of researches in this sphere is specified. Emphasis is placed on the need to improve the quality of research to determine: the essence of financial security of the banking sector and its varieties; challenges, internal and external, single and integrated / aggregate threats to the financial security of the banking sector and risks in this area, identification of sources of such threats, strength of their impact / damage / damage and ways to detect them, as well as appropriate methods of localization and neutralization; its relationship and interdependence with the financial security of commercial banks, the central bank, customers / counterparties of commercial banks, households, the region, the state, the security of payment systems and the financial system of the state in general. The author’s definition of financial security of the banking sector and classification of its varieties is given. It is proved that given the functional purpose of the banking sector, it is legitimate to talk about such components of financial security of the banking sector as: security of deposit, credit, investment, payment and settlement, currency exchange, insurance, brokerage, trust, security of financial flows and forms banking services (online, mobile, robotic banking, intelligent cross-channel information systems in cloud services compared to alternative lending (p2p lending) and alternative financing (crowdfunding and crowdfunding)), structured banking products.